Processing and properties of scaffolds based on calcium phosphate doped with magnesium, copper and zinc-ions coated with gelatin - Dragutinović Olivera Z.; Dimitrijević-Branković Suzana I.; Veljović Đorđe N. (Tehnika, 2023)
The main goal of this study was to examine the possibility for obtaining macroporous scaffolds with defined properties based on calcium phosphate doped with magnesium, copper and zinc ions, coated with gelatin, which would potentially provide controlled conditions for the formation of new bone tissue after implantation. As a first, multi-doped nanoparticles of hydroxyapatite (HAp), which represents the main component of the inorganic part of bone tissue, was synthesized by autoclaving the precursor solution obtained at a Ca/P molar ratio of 1.52. Calcium in the initial solution was partially replaced by ions of magnesium (5 mol.%), copper (0.4 mol.%) and zinc (0.4 mol.%). Obtained powder was further calcinated, the changes in the morphology of the powders during calcination at 1000 ̊ C were reflected in the transition of spherically agglomerated needle-like nanoparticles of the multi-doped hydroxy-apatite powder to a spherical grained morphology. Macroporous bioceramic structures were obtained using the sponge replica method, green macroporous samples made of calcinated multi-doped powder, polyvinyl alcohol and water were sintered at 1.370°Ϲ and 1.430°Ϲ. X-ray diffraction analysis deter-mined that the presence of magnesium in the structure of hydroxyapatite favors the phase transformation of HAp into b-tricalcium-phosphate (b-TCP), which contributed to the formation of the biphasic HAp/b-TCP system during the calcination of the powders, but also during the sintering of macroporous beads. Examination of the antimicrobial activity of the obtained macroporous supports against E. coli showed a more effective degree of inhibition compared to S. aureus. A significant increase in the compressive strength of sintered macroporous scaffolds was obtained after the formation of coating based on 7.5% gelatin solution.